2007
DOI: 10.1111/j.1365-2842.2006.01703.x
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of parafunctional oral habits in patients with cerebral palsy

Abstract: Cerebral palsy (CP) is one of the most frequent conditions encountered in the daily practice of dentists who treat special-needs patients and it seems that parafunctional oral habits are often present in such individuals. The aim of this study was to investigate the frequency of occurrence of parafunctional habits in individuals with CP. Sixty-five patients with CP were evaluated through a questionnaire and clinical observation, regarding the following habits: pacifier-sucking, finger-sucking, biting objects, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
89
1
17

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(112 citation statements)
references
References 15 publications
5
89
1
17
Order By: Relevance
“…Previous studies reported that individuals with cognitive impairment are more prone to this parafunction due to spasticity (an increase in muscle tone at the time of muscle contraction caused by an abnormal neurological condition -the spastic muscles are more resistant to contraction than normal muscles and also require more effort to relax and remain contracted for a period of time). [10][11][12][13] However, recent studies have found that the prevalence of SB is similar between such individuals and control individuals matched for age. 6,17 As a result of different study methods, clinical criteria and the populations studied, the reported prevalence of SB varies significantly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported that individuals with cognitive impairment are more prone to this parafunction due to spasticity (an increase in muscle tone at the time of muscle contraction caused by an abnormal neurological condition -the spastic muscles are more resistant to contraction than normal muscles and also require more effort to relax and remain contracted for a period of time). [10][11][12][13] However, recent studies have found that the prevalence of SB is similar between such individuals and control individuals matched for age. 6,17 As a result of different study methods, clinical criteria and the populations studied, the reported prevalence of SB varies significantly.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] Only a few studies have investigated the diverse aspects related to SB in patients with physical and/ or cognitive impairments. [10][11][12][13] Recent studies found a higher prevalence in individuals with Down syndrome when compared to individuals without cognitive impairment. Additionally, SB appeared to affect individuals with cerebral palsy twice as much as control individuals.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the present study daytime biting hard on the teeth or grinding the teeth was less than half as frequent as the reported frequency of teeth grinding at night. 28,29 (29) 2 (40) 13 (100) 0 (10) 1 (6) 3 (25) 2 (100) 11 (100) 17 ( (14) 2 (40) 9 (69) 0 (0) 2 (12) 2 (17) 1 (50) 8 (73) 12 (23) 5 -Oral motor function 5 (36) 5 (38) 5 (71) 4 (80) 13 (100) 3 (30) 8 (47) 10 (83) 2 (100) 11 (100) 34 (65) A Stick out your tongue as far as you can 0 (0) 2 (15) 1 (14) 2 (40) 13 (100) 1 (10) 1 (6) 3 (25) 2 (100) 11 (100) 18 ( (80) 13 (100) 3 (30) 8 (47) 10 (83) 2 (100) 11 (100) 34 (65) C Blow up your cheeks and hold for at least 3s 5 (36) 5 (38) 3 (43) 4 (40) 13 (100) 1 (1...…”
Section: Discussionmentioning
confidence: 99%
“…The current study also found a higher prevalence of anterior open bite and deep bite among the children with neuropsychological disabilities than sensory and physical disabilities. Since the group comprises Down's syndrome, mentally retarded and cerebral palsy subjects, the open bite may be attributed to the oral habit of projecting the tongue against the teeth and frequent episodes of upper air way infection which lead to a greater prevalence of mouth breathing and malocclusions, including anterior open bite [37]. These features are common in cerebral palsy and mentally retarded patients.…”
Section: Discussionmentioning
confidence: 99%
“…Neuropsychological disabilities comprising of mental retardation, autism, Down's syndrome and Attention deficit/hyperactive disorders is the group of disabilities frequently reported to have high prevalence of malocclusions by previous studies. This may be contributed by underdevelopment of oral facial musculature [36,37] and presence of oral dysfunction and parafunctions of masticatory system among some of these children [35].…”
Section: Discussionmentioning
confidence: 99%